Application Of Problem Based Learning Model To Improve Student Learning Outcomes In Ips Subjects Grade 8 Mts Singkawang Country - Decki Parjuanto Sarono Putra; Hasni Hasni; Andi Tenri Sumpala (Universitas Negeri Makassar, 2022)
This research is tofind out the application of problem based learning to the learning outcomes of students in grade 8 MTs Negeri Singkawang. This study is a classroom action research type of classroom action research. Data collection techniques using research instruments, namely observation, interviews, tests and documentation. This study produced data on student learning outcomes in social studies subjects in the 8th grade of MTs Negeri SIngkawang before being applied to PTK only achieving completeness 35,71% with an average value of 61,42. Students who reach the KKM standard are only 5 students while those that have not reached as many as 9 students. In the first cycle, student reached the minimum standard were 6 students, while those that had not reached the minimum standard scorewere 8 students with an average score of 63,57 with learning completeness of 42,85%. Whereas in the second cycle, the number of students who reached the minimum standard score were 12 students and students who had not reached the minimum standard score standard were 2 students with an average score of 84,28 and the level of completeness was 85,71%. Then it can be concluded that there is a significant effect on the application of the problem based learning model to student learning outcomes.